Mechanosensing in macrophages and dendritic cells in steady-state and disease - Lee, Megan; Du, Huixun; Winer, Daniel A.; Clemente-Casares, Xavier; Tsai, Sue (Frontiers in Cell and Developmental Biology, 2022)
Macrophages and dendritic cells are myeloid cells that play critical roles in immune responses. Macrophages help to maintain homeostasis through tissue regeneration and the clearance of dead cells, but also mediate inflammatory processes against invading pathogens. As the most potent antigen-presenting cells, dendritic cells are important in connecting innate to adaptive immune responses via activation of T cells, and inducing tolerance under physiological conditions. While it is known that macrophages and dendritic cells respond to biochemical cues in the microenvironment, the role of extracellular mechanical stimuli is becoming increasingly apparent. Immune cell mechanotransduction is an emerging field, where accumulating evidence suggests a role for extracellular physical cues coming from tissue stiffness in promoting immune cell recruitment, activation, metabolism and inflammatory function. Additionally, many diseases such as pulmonary fibrosis, cardiovascular disease, cancer, and cirrhosis are associated with changes to the tissue biophysical environment. This review will discuss current knowledge about the effects of biophysical cues including matrix stiffness, topography, and mechanical forces on macrophage and dendritic cell behavior under steady-state and pathophysiological conditions. In addition, we will also provide insight on molecular mediators and signaling pathways important in macrophage and dendritic cell mechanotransduction.